PENGUATAN KEBERLANJUTAN USAHA IKAN SALAI BENGKULU MELALUI PENGAWET ALAMI GAMBIR, STANDARISASI PROSES, DAN BRANDING DIGITAL - Sari, Selly Ratna; Bilyaro, Woki; Surawan, Fitri Electrika Dewi (Jurnal Abdi Insani, 2025)
The Business Partner Profile of Ikan Salai Bengkulu is a home industry engaged in fish smoking, located in Kandang Limun, Muara Bangkahulu, Bengkulu, approximately ±1.3 km from the University of Bengkulu. The partner’s problems include production and marketing aspects; although it has potential, the partner faces several challenges that need to be addressed immediately. The partner produces smoked products with the flagship product being smoked fish; the use of a smoking cabinet maintains the quality of the smoked fish, and the partner has not yet used natural PKM to increase fish production. This PKM program aims to improve the production capacity and competitiveness of Bengkulu’s traditional smoked fish business through the application of appropriate technology, hygienic processing, and digital marketing strategies toward an educational industry. Methods include socialization, training, and direct practice. Activities include training with material or education on natural preservatives, raw material quality, and digital marketing. The activities continue with practical sessions including the preparation of smoked fish using gambier soaking as an innovative preservation method. Partners are also trained to use appropriate technological tools, including portable smoking cabinets and vacuum sealer loans for hygienic packaging. This service is expected not only to develop the group or business but also to become a model educational industry. This is because it starts with the education provided, the technological tools used, and produces functional products moving toward downstream industry. The partner’s products underwent proximate laboratory testing to support attractive packaging, showing carbohydrate content of 1.31%, protein 47.52%, and minerals 12.52%. Moisture content produced includes below 20% and above 20% according to orders. Then the color and texture results are good after applying natural preservatives such as gambier. The activities increased from only 10 kg to 20 kg that can be made in the smoking cabinet; the use of portable smoking cabinets makes it more hygienic, with even heat and maintained quality, and the implementation of digital marketing can expand sales and provide education.